The effects of temperature difference and compressive force to the electrical characterization of peltier cell for artificial concentrated solar power thermoelectric application / Baljit Singh ... [et al.] - Baljit Singh (Faculty of Mechanical Engineering & UiTM Press, 2014)
Concentrated thermoelectric generating system uses concentrated solar radiations as passive heat source to operate the thermoelectric module for thermoelectricity generation. The pre-perquisite of thermoelectric effect is to provide a temperature difference across the thermoelectric cell by installing active water-cooling device on the opposite side of the heated panel Thermoelectric cells are known to have low energy conversion (3-5%) hence optimizing the parameters associated with the operation of the thermoelectric cells is very important to improve the overall system efficiency. Thermal contact interfacial tests were carried out to determine the optimum compressive stress for greater thermoelectric power generation as well as to avoid cell damage under mechanical compression. In this paper, a series of parametric studies for output power, output current, output voltage and open circuit voltage were conducted indoor on a Peltier-type thermoelectric cell to investigate the thermoelectric performance under different conditions. The aim of this study is to achieve optimum setting prior to the development of the final test rig which will be tested outdoor. The indoor experiments have shown that there is a limit to the overall cooling water flow rate and the compressive force applied to the thermoelectric cells under optimal operation. At the optimal parametric consideration of 11.11 ml/s cooling water flow rate and 245.25 kPa compressive forces, the thermoelectric cell was able to produce output power of 4.19W while operating at temperature difference of94.55°C and efficiency of 2.62% (21.88% of Carnot efficiency).